Dominica : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
The economy is predominantly agricultural, although some degree of diversification has taken place in recent years toward tourism, communications, and financial services. The performance of the main agricultural activity, banana production and exports, has steadily deteriorated since the early 1990s and has adversely affected developments in other sectors. In the external sector, the current account of the balance of payments has shown a marked deterioration in recent years. The saving-investment balance showed a marked deterioration during 1999-2000.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Dominica